Assessment of the knowledge of university young people regarding sexually transmitted infections (Research, Society and Development, 2021)
According to the World Health Organization (WHO), about 1 million new sexually transmitted infections (STIs) occur daily. However, these are considered a worldwide public health problem. In Brazil, cases of STIs have grown, especially among young people. Therefore, this study aimed to assess the level of knowledge of young university students about STIs. The research universe consisted of 154 young people aged between 18 and 29 years old, who answered an online and self-applied questionnaire. A booklet and a folder were made available to participants to guide them about STIs. In most questions, general knowledge of the participants was observed. However, regarding indirect forms of transmission, participants showed a lack of knowledge when compared to forms of direct transmission, which are more publicized. As well as an obscurantism regarding some forms of clinical manifestation, and some STIs. In addition, a significant portion of the participants showed embarrassment when talking about the subject. And despite the majority claiming to be safe for sex life with prior knowledge, most participants said they would like to receive more information about STIs.